1979
DOI: 10.1007/bf02590763
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic changes of the extra-ocular muscles in man

Abstract: Axonal and myelin changes of the degenerative type were found in the extra-ocular muscles of 21 out of 23 diabetics of all ages (30--74 years). In all these 21 cases both axonal and myelin changes were observed; they did not correlate with the duration, degree of severity or treatment of diabetes. In 19 of the 23 cases (82.6%) nervous changes were accompanied by vascular changes. In 10 controls (50--80 years) nervous and vascular changes were of a slight degree. The findings of the alteration of peripheral ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Besides the authors identified environmental toxic exposure and hypertriglyceridemia, but not glucose tolerance or IR as significant risk factors of chronic idiopathic polyneuropathy [16]. The relation between blepharoptosis and DM is well-known, conversely there are only some not controlled studies between blepharoptosis and manifestations of prediabetes [17,18]. Our data documented a strong linkage between blepharoptosis and glucose metabolism abnormality (IGT, DM, IR) in patients with normal fasting glycaemia.…”
Section: Discussionsupporting
confidence: 49%
“…Besides the authors identified environmental toxic exposure and hypertriglyceridemia, but not glucose tolerance or IR as significant risk factors of chronic idiopathic polyneuropathy [16]. The relation between blepharoptosis and DM is well-known, conversely there are only some not controlled studies between blepharoptosis and manifestations of prediabetes [17,18]. Our data documented a strong linkage between blepharoptosis and glucose metabolism abnormality (IGT, DM, IR) in patients with normal fasting glycaemia.…”
Section: Discussionsupporting
confidence: 49%
“…Table 2 summarizes the studies currently available through database searches. Three studies, for which we were unable to retrieve the original references, have not been included (Ellenberg, 1977;Montenero & Donatoni, 1973;Zrustova, Rostlapil, & Kabrhelova, 1978).…”
Section: Clinical Studiesmentioning
confidence: 97%
“…Findings of some histopathological studies are consistent with this hypothesis. Zrustova et al [9], in a study of 23 diabetic patients, evaluated the changes in the extraocular muscles and their innervations and reported that diabetics had degenerative axonal changes and abnormal myelin sheath swelling compared with nondiabetic controls. These neural changes did not correlate with duration, degree of severity, treatment of the disease or the presence of diabetic retinopathy [9].…”
Section: Discussionmentioning
confidence: 99%
“…Zrustova et al [9], in a study of 23 diabetic patients, evaluated the changes in the extraocular muscles and their innervations and reported that diabetics had degenerative axonal changes and abnormal myelin sheath swelling compared with nondiabetic controls. These neural changes did not correlate with duration, degree of severity, treatment of the disease or the presence of diabetic retinopathy [9]. In a study evaluating the extraocular muscles and their innervations in diabetic patients with oculomotor nerve palsy, hyaline thickening of intraneural arterioles and localized nerve changes consistent with ischemia such as necrosis or interstitial edema have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%